Predictors of caregiver burden in mothers of children with leukemia and cerebral palsy. Issue 1 (2nd January 2019) - Boztepe, Handan; Çınar, Sevil; Ay, Ayşe; Kerimoğlu Yıldız, Gizem; Kılıç, Cengiz
Abstract: Objective: Caring for a sick child can lead to considerable burden in the caregiver. Comparative studies of burden in mothers of children with different types of disorders are rare. Methods: We assessed levels of and risk factors for burden in mothers of children with leukemia (n: 70) or with cerebral palsy (CP) (n: 69). Subjects were recruited from two hospitals in Ankara. Results: Levels of burden or depression were not different between groups. Burden was predicted by the presence of depression in the mother and severity of illness in both groups. In the leukemia group, mothers reported higher burden if the child was male or younger; no such relationship was observed in the CP group. Conclusion: Our results show that type of illness has an effect on levels of burden. Mothers of children with leukemia should receive more attention, especially if their child is male or younger, to take preventive measures against burden.